Determinants of Factors Affecting the Incidence of Patients Discharged on Their Own Request in the Inpatient Room of the Sahabat Keluarga Clinic: A Qualitative Study - Efin Sulistyorini; Sentot Imam Suprapto; Yenny Puspitasari (Babali Nursing Research, 2023)
Introduction: Discrepancies in patient expectations of hospital or clinic services can cause patients to return home or be reluctant to use the service again. This is certainly detrimental to both parties, the hospital or clinic will lose because of reduced income and the patient or family feels disadvantaged because treatment has not been completed. The purpose of this study was to explore the influence of knowledge, family support and the cost of care on the incidence of patients returning home at their own request in the Inpatient Room of the Sahabat Keluarga Clinic. Methods: This research design is a qualitative study with a phenomenological approach with the focus of the research directed at exploring the influence of knowledge, family support and the cost of care on the incidence of patients returning home at their own request in the Inpatient Room of the Sahabat Keluarga Clinic. In addition, the qualitative approach is expected to reveal the situation and problems faced in these activities. The informants in this study were the owner or person in charge of the clinic totaling 12 (Twelve) people. Results: Knowledge has an influence on the incidence of patients going home at their own request in the Inpatient Room of the Sahabat Keluarga Clinic. Family support has an influence on the incidence of patients discharged at their own request in the Hospitalization Room of the Sahabat Keluarga Clinic. The cost of care has an influence on the incidence of patients discharged at their own request in the Hospitalization Room of the Sahabat Keluarga Clinic. Conclusion: It is expected that patients actively communicate with medical personnel and the care team to understand health conditions better. In addition, do not hesitate to ask questions and seek further information about the treatment plan that will be carried out.